2019
DOI: 10.3390/en12122383
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Hydrothermal Carbonization (HTC) Hydrochar from Sewage Sludge

Abstract: As a treatment method of sewage sludge, the hydrothermal carbonization (HTC) process was adopted in this work. HTC has a great advantage considering the economic efficiency of its process operation due to its reduced energy consumption and production of solid fuel upgraded through the increased fixed carbon and heating value. The ash of sewage sludge, however, contains up to 52.55% phosphate, which degrades the efficiency of the thermochemical conversion process such as pyrolysis, combustion, and gasification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…While multiple studies focused on nutrients recovery such as phosphorous [28][29][30] or probed the impact of processing conditions on the solid and energy yields of hydrochars produced from the HTC of sludge from one withdrawal point in the wastewater treatment (WWT) process [23,[31][32][33][34][35][36][37][38][39], the impact of upstream WWT processes on hydrochars is often not part of the experimental design. Thus, a primary goal of the present work was to determine the most viable point in the WWT process to employ HTC for sludge treatment from a solid fuel production and potential nutrient recovery standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…While multiple studies focused on nutrients recovery such as phosphorous [28][29][30] or probed the impact of processing conditions on the solid and energy yields of hydrochars produced from the HTC of sludge from one withdrawal point in the wastewater treatment (WWT) process [23,[31][32][33][34][35][36][37][38][39], the impact of upstream WWT processes on hydrochars is often not part of the experimental design. Thus, a primary goal of the present work was to determine the most viable point in the WWT process to employ HTC for sludge treatment from a solid fuel production and potential nutrient recovery standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…However, when an acid-leaching step was added, lignite-like upgraded hydrochars were obtained and at the same time the acidic leachate was precipitated with the use of CaO to yield a total P content close to 42 mg g −1 [62]. The upgrading of hydrochar properties has also been confirmed when organic acids (e.g., oxalic acid) were used to extract and bind P [63]. It is worth noting that in these recent studies, HTC was performed with the natural water content of sewage sludge, without the addition of surplus water.…”
Section: Citespace Recent Scientometric Analysis (2018-2020)mentioning
confidence: 91%
“…The reactor was loaded with a 1:8 dry sample to water ratio (constant mass of 50 g of sludge on dry basis (db) or 98.4 g and 96.1 g on wet basis (wb) for PS and BS, respectively). The individual experiments were produced at reaction temperatures of 180, 200, 220 and 240 • C and a residence time of three hours, which is considered to be a typical representative retention time for reactions [2,3,24]. The process parameters were selected in accordance to different literature reports [3,25,26], which concluded that a 1:8 ratio enhances the decomposition reaction, which leads to a higher mass loss and heating value when compared to lower ratios.…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%